2021
DOI: 10.1371/journal.pone.0249584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical features, and outcomes of SARS-CoV-2 infection in pregnant women with or without mild/moderate symptoms: Results from universal screening in a tertiary care center in Mexico City, Mexico

Abstract: The perinatal consequences of SARS-CoV-2 infection are still largely unknown. This study aimed to describe the features and outcomes of pregnant women with or without SARS-CoV-2 infection after the universal screening was established in a large tertiary care center admitting only obstetric related conditions without severe COVID-19 in Mexico City. This retrospective case-control study integrates data between April 22 and May 25, 2020, during active community transmission in Mexico, with one of the highest COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 41 publications
5
45
4
2
Order By: Relevance
“…SARS-CoV-2 infection in pregnancy seems to be associated with increased risks of preeclampsia, stillbirth, preterm birth, premature rupture of membrane and NICU admission. In the Cardona-Pérez et al study, an increased risk of preeclampsia in women with SARS-CoV-2 infection was found [16]. In our study group, only one woman (0.01% of respondents) was suspected of having pre-eclampsia, which does not allow us to confirm the conclusion of quoted Cardona-Pérez et al [16] the thesis that SARS-CoV-2 infection increases the risk of pre-eclampsia.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…SARS-CoV-2 infection in pregnancy seems to be associated with increased risks of preeclampsia, stillbirth, preterm birth, premature rupture of membrane and NICU admission. In the Cardona-Pérez et al study, an increased risk of preeclampsia in women with SARS-CoV-2 infection was found [16]. In our study group, only one woman (0.01% of respondents) was suspected of having pre-eclampsia, which does not allow us to confirm the conclusion of quoted Cardona-Pérez et al [16] the thesis that SARS-CoV-2 infection increases the risk of pre-eclampsia.…”
Section: Discussioncontrasting
confidence: 77%
“…In the Cardona-Pérez et al study, an increased risk of preeclampsia in women with SARS-CoV-2 infection was found [16]. In our study group, only one woman (0.01% of respondents) was suspected of having pre-eclampsia, which does not allow us to confirm the conclusion of quoted Cardona-Pérez et al [16] the thesis that SARS-CoV-2 infection increases the risk of pre-eclampsia. In this study, also increased risk of premature rupture of membrane (PROM) was reported.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This large referral center for perinatal health care has one of the highest prevalences of SARS-CoV-2 among pregnant women, around 30%. However, less than 3% of patients were symptomatic [ 13 , 14 ]. The mild to moderate symptoms associated with SARS-CoV-2 infection were headache, dyspnea, myalgia, and olfactory/gustatory dysfunction [ 13 ].…”
Section: Introductionmentioning
confidence: 99%